Adaptive/Appropriative Reuse in Neo-Victorian Fiction: Having One's Cake and Eating It Too - Marie-luise Kohlke (Interventions: Rethinking the Nineteenth Century, 2017)
This chapter considers neo-Victorian fiction in terms of notions of 'reuse' more commonly applied to the repurposing, renovation, and modernisation of historical buildings, exploring the multiple heterogeneous cultural utilisations of the neo-Victorian and the audience appetites it serves.